2018
DOI: 10.1155/2018/6715813
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Steel Fibers and Nanosilica Modified Crumb Rubber Concrete

Abstract: Crumb rubber concrete (CRC) is an environment-friendly material using crumb rubber as a composition of cement concrete. It provides an alternative method for recycling of waste tires scientifically. CRC exhibits numerous advantages compared to ordinary concrete. However, the application of CRC is limited due to its low compressive and tensile strengths. is paper puts forward a new modified method by adding steel fibers and nanosilica in CRC. Material properties' testing of eighteen concrete mixtures was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Based on the test data from this paper and previous research [22,23,30,32,33,43,[45][46][47][48], the relationship between the ratio of (f cu − f c0 )/f c0 and λ f and v N is shown in Figure 10, where f cu and f c0 are the cube compressive strength of SFNS-CRC and CRC and λ f is the characteristic coefficient of steel fibers. Although the experimental data look like dispersed, the ratio of (f cu − f c0 )/f c0 has an increasing tendency with the increasing λ f and v N , respectively.…”
Section: Compressive Strengthmentioning
confidence: 93%
See 1 more Smart Citation
“…Based on the test data from this paper and previous research [22,23,30,32,33,43,[45][46][47][48], the relationship between the ratio of (f cu − f c0 )/f c0 and λ f and v N is shown in Figure 10, where f cu and f c0 are the cube compressive strength of SFNS-CRC and CRC and λ f is the characteristic coefficient of steel fibers. Although the experimental data look like dispersed, the ratio of (f cu − f c0 )/f c0 has an increasing tendency with the increasing λ f and v N , respectively.…”
Section: Compressive Strengthmentioning
confidence: 93%
“…However, Fu et al [23] found that the effect of concrete containing rubber crumbs on compressive strength depends on the rubber content. e decline in compressive strength due to a high amount of fiber dosage in CRC might be associated with the poor compactness [43].…”
Section: Effects Of Steel Fibers and Nanosilica On Compressivementioning
confidence: 99%
“…e results showed that both fibers increased the energy absorption capacity of cement mortar. Wang et al [19] studied a CRC that was modified by adding steel fibers and nanosilica. e test results showed that the modified CRC with 1.0% steel fiber content had relatively high compressive and splitting tensile strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it enhances the absorption energy and expands the region beneath the pressure curve. Several methods have already been introduced into the literature for improving the engineering properties of rubberized concrete, including pretreating the rubber with a NaOH solution (Youssf et al, 2016;Wang et al, 2018), adding materials like silica fume and steel fiber (Onuaguluchi and Panesar, 2014), and pre-coating with limestone powder (Segre et al, 2002). Increased surface roughness of rubber aggregates is the main objective of using NaOH, which also aims to lessen the severe negative effects of the insufficient bonding between rubber particles and cement paste.…”
Section: Tests Onmentioning
confidence: 99%